On transfinite diameters in $\mathbb{C}^{d}$ for generalized notions of degree - Levenberg, Norman; Wielonsky, Franck (MATHEMATICA SCANDINAVICA, 2021)
We give a general formula for the $C$-transfinite diameter $δ_C(K)$ of a compact set $K\subset \mathbb{C}^2$ which is a product of univariate compacta where $C\subset (\mathbb{R}^+)^2$ is a convex body. Along the way we prove a Rumely type formula relating $δ_C(K)$ and the $C$-Robin function $ρ_{V_{C,K}}$ of the $C$-extremal plurisubharmonic function $V_{C,K}$ for $C \subset (\mathbb{R}^+)^2$ a triangle $T_{a,b}$ with vertices $(0,0)$, $(b,0)$, $(0,a)$. Finally, we show how the definition of $δ_C(K)$ can be extended to include many nonconvex bodies $C\subset \mathbb{R}^d$ for $d$-circled sets $K\subset \mathbb{C}^d$, and we prove an integral formula for $δ_C(K)$ which we use to compute a formula for $δ_C(\mathbb{B})$ where $\mathbb{B}$ is the Euclidean unit ball in $\mathbb{C}^2$.